Biodegradation of phenol using cold-adapted antarctic bacterial community from soil - Tengku Mazuki, Tengku Athirrah (2023)
Phenol, a substance that is extremely poisonous to most living organisms, is often associated with the products of and waste produced by the chemical and petroleum industries. Contamination involving phenolic compounds has been reported in extreme environments, including the Antarctic. In such environments, the use of indigenous microbes capable of degrading phenol has proven successful even though the chemical is toxic to most microbes. This study focuses on the ability of an Antarctic native bacterial consortium to tolerate and degrade a high concentration of phenol. Based on preliminary screening of bacterial consortia obtained from 28 Antarctic soil samples, one consortium (BS27), capable of completely degrading 0.5 g/L phenol within 20 d at 10℃, was selected for further study. Optimisation of growth and phenol degradation conditions for this consortium was carried out using conventional one-factor-at-a-time (OFAT) and statistical response-surface methodology (RSM) approaches. Based on the results from OFAT, the optimum conditions for phenol degradation were pH 7, 2.0 g/L NaCl, the use of ammonium sulphate as nitrogen source at 1.0 g/L, initial phenol concentration of 0.5 g/L and temperature of 15℃. The consortium achieved 100% degradation of 0.5 g/L phenol under conditions predicted by RSM at 15℃, pH 7.50, 0.8 g/L NaCl and 1.7 g/L ammonium sulphate. Co-exposure to heavy metals identified that the two heavy metals that showed the highest inhibitory effect on phenol degradation were mercury (Hg) and silver (Ag), while three others, nickel (Ni), chromium (Ch) and cobalt (Co) caused bacterial growth and phenol degradation inhibition of more than 50%. Ag, Hg, Co, Cr and Ni had half-maximal inhibitory concentrations (IC50) of 0.01221 ppm, 0.05873 ppm, 3.546 ppm, 0.3063 ppm and 0.7128 ppm, respectively. Metagenomic analyses were applied to both the originally isolated consortium and that which had developed after optimisation to assess the contained diversity of each and help identify the components likely to be involved in enhancing phenol biodegradation. These revealed a dominant microbial community, which included Proteobacteria, Bacteroidetes, Actinobacteria and Firmicutes amongst others. Study of bacterial growth kinetics revealed the Yano model to be the best-fitting model with a calculated coefficient of maximum rate (μmax) of 2.277 h-1. The data obtained increase knowledge of Antarctic bacterial biodiversity and contribute to assessing the potential of native Antarctic bacteria in the bioremediation of phenol-contaminated sites in extreme environments.